Why Healthcare Providers Should Focus on the Fertility of AYA Cancer Survivors: It’s Not Too Late! - Murphy, Devin; Orgel, Etan; Termuhlen, Amanda; Shannon, Susan; Warren, Krista; Quinn, Gwendolyn P. (Frontiers in Oncology, 2013)
Reproductive health among cancer survivors is an important quality of life issue. Certain cancer therapies have known fertility risks. There is an existing cohort of AYA cancer survivors that, seen less frequently in clinical care settings than active patients, are likely not having discussions of fertility and other reproductive health issues. A survivor or healthcare provider can easily assume that the window of opportunity for fertility preservation has passed, however emerging technology has examined the close relationship between fertility and other late effects to conclude that assessment during survivorship is warranted. Some fertility preservation procedures have also been shown to mitigate these late effects. This review explores the relevance of ongoing fertility discussions in the AYA survivorship population.